Preconditioning with cell-free DNA prevents DSS-colitis by promoting cell protective autophagy. (10th May 2020) - Constantinovits, Miklós; Sipos, Ferenc; L Kiss, Anna; Műzes, Györgyi
Abstract : Presence of cell-free DNA (cfDNA) in sera of patients with inflammatory bowel diseases (IBD) is a long-known fact. The biological effect of cfDNA administration on cellular autophagy within normal and inflammatory circumstances remains unclear. In this study, the effects of intravenous cfDNA pretreatment on autophagy response were studied in dextran sulfate sodium (DSS)-induced acute experimental colitis. Selected proinflammatory cytokine and autophagy-related gene and protein expressions were compared with clinical and histological activity parameters, and with transmission electron microscopic evaluations. A single intravenous dose of cfDNA pretreatment with cfDNA from colitis exhibited beneficial response concerning the clinical and histological severity of DSS-colitis as compared with effects of normal cfDNA. Pretreatment with colitis-derived cfDNA substantially altered the gene and protein expression of several autophagy and inflammatory cytokine genes in a clinically favorable manner. Autophagy in splenocytes is also altered after colitis-derived cfDNA pretreatment. During the process of acute colitis, the subsequent inflammatory environment presumably results in changes of cfDNA with the potential to facilitate cell protective autophagy. Understanding the molecular mechanisms behind the impact of colitis-associated autophagy, and elucidating alterations of the interaction between autophagy and innate immunity caused by nucleic acids may provide further insight into the etiology of IBD. By targeting or modifying cfDNA, novel anti-inflammatory therapies may be developed.